2015
DOI: 10.1097/hjh.0000000000000701
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid and the risk of cardiovascular and renal disease

Abstract: Substantial evidence suggests that chronic hyperuricemia is an independent risk factor for hypertension, metabolic syndrome, chronic kidney disease (CKD) and cardiovascular diseases. This highlights the need for greater attention to serum uric acid levels when profiling patients, and suggests that the threshold above which uricemia is considered abnormal is 6  mg/dl, in light of the available evidence. Another important question is whether lowering serum uric acid can improve cardiovascular and renal outcomes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
290
1
52

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 426 publications
(351 citation statements)
references
References 110 publications
(125 reference statements)
8
290
1
52
Order By: Relevance
“…Psoriazisdeki artmış enflamasyonun epitelyal disfonksiyona neden olduğu ve buna bağlı olarak kardiyovasküler hastalık riskinde artışa neden olduğu düşünülmektedir 2,[14][15][16] . Ürik asit hipertansiyon, metabolik sendrom ve aterosklerotik kalp hastalıkları gibi birçok durum ile ilişkili olduğu gösterilen metabolik bir belirteçtir [6][7][8] . Ürik asit ile metabolik sendrom ve komponentleri…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Psoriazisdeki artmış enflamasyonun epitelyal disfonksiyona neden olduğu ve buna bağlı olarak kardiyovasküler hastalık riskinde artışa neden olduğu düşünülmektedir 2,[14][15][16] . Ürik asit hipertansiyon, metabolik sendrom ve aterosklerotik kalp hastalıkları gibi birçok durum ile ilişkili olduğu gösterilen metabolik bir belirteçtir [6][7][8] . Ürik asit ile metabolik sendrom ve komponentleri…”
Section: Discussionunclassified
“…Hatta yeni çalışmalarda psoriaziste sistemik bir enflamasyonun geliştiği ve buna bağlı olarak psoriazisin metabolik sendrom ile kardiyovasküler hastalıklarla ilişkili olduğu gösterilmiştir [2][3][4][5] . Önemi son yıllarda daha iyi anlaşılmış metabolik bir marker olan ürik asitin metabolik sendrom, hipertansiyon ve kardiyovasküler hastalıklarla ilişkili olduğu düşünülmektedir [6][7][8][9] . Psoriazis hastalarında ürik asit yüksekliği eskiden beri üzerinde çalışılan ve iyi bilinen bir durumdur 10,11 .…”
Section: Introductionunclassified
“…Hyperuricemia was associated with deleterious effects on endothelial dysfunction, oxidative metabolism, platelet adhesiveness, hemorheology, and aggregation 2,3 . A pathogenetic role of hyperuricemia in the progression of renal disease has been proposed based of mechanisms activated by high levels of uric acid, mainly at the vascular level 4 .…”
Section: Links Between Uric Acid and Vascular-renal Diseasementioning
confidence: 99%
“…Serum uric acid (SUA) level has been shown to be associated with an increased risk of cardiovascular morbidity and mortality 1 , and it was found to be correlated with hypertension in children and adults 2,3 . The role of uric acid in blood-pressure (BP) control has been investigated to understand whether hyperuricemia is an independent risk factor, so that a urate lowering therapy should be used to reduce cardiovascular risk, or whether it represents a marker of other prognostic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…The role of uric acid in blood-pressure (BP) control has been investigated to understand whether hyperuricemia is an independent risk factor, so that a urate lowering therapy should be used to reduce cardiovascular risk, or whether it represents a marker of other prognostic abnormalities. It has also been observed that urate lowering drugs may have an antihypertensive effect 1 . This article will briefly review the evidence of the link between hypertension and SUA and will discuss the impact of uric acid on BP lowering therapy.…”
Section: Introductionmentioning
confidence: 99%